Application of an in vitro digestion model for 210Po bioaccessibility assessment in seafood. (26th October 2017) - Roselli, Carla; Desideri, Donatella; Feduzi, Laura; Ugolini, Lucia; Meli, Maria Assunta
Abstract: This study aims to investigate the bioaccessibility of 210 Po in seafood and the impact of food preparation on this radionuclide. Polonium bioaccessibility is the fraction of 210 Po mobilised from food matrices into digestive extractants when applying an in vitro digestion model. The degree of bioaccessibility of 210 Po in food has important implications for estimating ingestion doses from this radionuclide. The simulation of gastrointestinal digestion was divided into three stages through the use of synthetic saliva, gastric and bile–pancreas solutions. Following pre-treatment with a saliva solution, raw and cooked seafood samples underwent one of the following treatments: (a) simulated gastric digestion only or (b) simulated complete gastrointestinal digestion (gastric digestion followed by bile-pancreas digestion). No significant difference ( P  > 0.05) in 210 Po mobility was found between samples that underwent gastric digestion compared to those that only underwent gastro-intestinal digestion. However, a significant difference ( P  < 0.05) in 210 Po bioaccessibility was found between raw and cooked seafood undergoing both gastric and gastro-intestinal digestion.